Universality of the evaporation/condensation transition - Nuβbaumer, Andreas; Bittner, Elmar (Physics procedia, 2010)
By making use of the well-known lattice-gas interpretation, we investigated the evaporation/condensation transition through Monte Carlo simulations of the square lattice Ising model with nearest-neighbour couplings and periodic boundary conditions. The particle density can be varied by choosing different fixed magnetisations. In the analysis of our data we followed recent analytical work by Biskup et al. [Europhys. Lett. 60 (2002) 21], who also used the Ising model to study liquid-vapour systems at a fixed excess δN of particles above the ambient gas density in the limit of large system sizes. By identifying a dimensionless parameter Δ(δN), they showed that for Δ<Δc all excess is absorbed in background fluctuations (“evaporated” system), while for Δ>Δc a single large droplet of the dense phase occurs (“condensed” system). Besides the threshold value Δc also the fraction λ of excess particles forming the droplet is given explicitly. To test the applicability of these asymptotic results to practically accessible system sizes, we measured the volume of the largest minority droplet, corresponding to a fluid drop, for various L×L lattices with L=40,…,640. Using analytic values for the spontaneous magnetisation m0, the susceptibility χ and the Wulff interfacial free-energy density τW for the infinite system, we were able to determine Δc and λ numerically in very good agreement with the theoretical prediction. We also discuss the associated free-energy barrier and its implication for multimagnetical simulations, and put these findings into context with the related droplet/strip transition respectively barrier.